2022
DOI: 10.2196/34863
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Recruitment Strategies of Latino Smokers: Secondary Analysis of a Mobile Health Smoking Cessation Randomized Clinical Trial

Abstract: Background Latinos remain disproportionately underrepresented in clinical trials, comprising only 2%-3% of research participants. In order to address health disparities, it is critically important to increase enrollment of Latino smokers in smoking cessation trials. There is limited research examining effective recruitment strategies for this population. Objective The purpose of this study was to compare the effectiveness of direct versus mass and high-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The abbreviated HSI2 consisted of 52 items that were distributed in ten factors as proposed in the original scale: Parental Stress, Occupation and Economic Stress, Marital Stress, Discrimination Stress, Immigration-Related Stress, Marital Acculturation Gap Stress, Health Stress, Language Related Stress, Pre-Migration Stress, and Family-Related Stress. The details of the clinical trial intervention and protocol have been reported in previous articles [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The abbreviated HSI2 consisted of 52 items that were distributed in ten factors as proposed in the original scale: Parental Stress, Occupation and Economic Stress, Marital Stress, Discrimination Stress, Immigration-Related Stress, Marital Acculturation Gap Stress, Health Stress, Language Related Stress, Pre-Migration Stress, and Family-Related Stress. The details of the clinical trial intervention and protocol have been reported in previous articles [ 27 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility efficiency ratio was the ratio of the number of individuals eligible to the number screened. [18][19][20] Enrollment efficiency ratio was the ratio of the number of individuals enrolled to the number screened. [18][19][20] Rates of eligibility and enrollment across the two recruitment methods were compared using chi-square tests.…”
Section: Assessmentsmentioning
confidence: 99%
“…[18][19][20] Enrollment efficiency ratio was the ratio of the number of individuals enrolled to the number screened. [18][19][20] Rates of eligibility and enrollment across the two recruitment methods were compared using chi-square tests. Differences in categorical variables were compared using Fisher exact test, while differences in continuous variables were compared using student's t-test.…”
Section: Assessmentsmentioning
confidence: 99%
“…Latinos also report a general lack of cultural sensitivity within existing Spanish language resources for smoking cessation [ 11 ]. Although barriers to accessing smoking cessation resources exist, when provided with access, Latinos are interested in participating in smoking cessation programs and in using smoking cessation treatments to support quit attempts [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, research on the development and implementation of interventions for smoking cessation among Latinos has been conducted [ 13 , 14 , 15 , 16 , 17 , 18 ]. For example, one study assessed the feasibility and acceptability of a culturally and linguistically adapted smoking cessation text messaging intervention among Latino adults who smoke [ 15 ].…”
Section: Introductionmentioning
confidence: 99%